Monitoring the Socio-Economic Impacts of COVID-19 on Djiboutian Households : Results from First Round of Survey - Mendiratta, Vibhuti; Gansey, Romeo Jacky; Duplantier, Anne; Konate, Sekou Tidani; Abdoulkader, Omar (World Bank, Washington, DC, 2020)
Djibouti had its first confirmed case of Coronavirus (COVID-19) on 18 March 2020. As an early response, the government suspended all in and out international passenger flights on March 18, 2020, closed schools and universities, and ordered a general lockdown starting from March 27, 2020. As of August 20, 2020, there were 5,374 confirmed cases of Coronavirus (COVID-19) in Djibouti, with fifty-nine reported deaths. Even though the total number of cases increased sharply in the last two weeks of May and early June, they declined considerably in July and August. This report focuses on the Coronavirus (COVID-19) impacts on households in Djibouti as of September 2020.